Development of Augmented Reality-Based Learning Media Using Assemblr EDU for Introducing Indonesian Traditional Musical Instruments in Junior High School Music Education - Aprianti, Yanti Nur; Karwati, Uus; Gunara, Sandie (Jurnal Paedagogy, 2026)
This study aims to develop and validate an Augmented Reality (AR)-based learning medium using Assemblr EDU for introducing Indonesian traditional musical instruments in Grade VIII music education. This study employed a Research and Development (R&D) method based on the 4D model, which consists of four stages: Define, Design, Develop, and Disseminate. The research was conducted at SMP Negeri 6 Banjar, West Java, involving 20 eighth-grade students. Data were collected through interviews, expert validation instruments, questionnaires, and post-tests, and analyzed using descriptive percentage analysis techniques. The developed product integrates 3D visualization, annotations, audio narration, and AR features that can be accessed through mobile devices. The validation results showed that the learning media achieved a score of 98.75% from media experts and 100% from subject matter experts, indicating a highly valid category. The implementation results demonstrated that the media was feasible for classroom use and facilitated interactive learning about traditional musical instruments from various regions of Indonesia. These findings indicate that AR technology has the potential to transform traditional music learning by enabling students to interact directly with virtual representations of musical instruments. Consequently, AR-based learning media can provide a more immersive, accessible, and meaningful learning experience while supporting efforts to preserve Indonesia’s traditional musical heritage.